APLIKASI TOKO ALAT MUSIK DENGAN KEAMANAN PASSWORD KRIPTOGRAPI KODE GESER - Purwanti; Nazelliana, Dian; Dwi Nurcahya, Saputra (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This encryption technique is used to secure customer data by shifting the characters in the message. This technique is used in musical instrument store applications to ensure the security of customer information such as personal details and financial information. This application was made to make it easier for users to find and buy the desired musical instrument online. Users can create accounts, enter personal information, and generate passwords that are encrypted with slide code cryptography. Customer information will be stored securely on the application server, only to be accessed with the correct password. Password security is very important to protect customer personal data and prevent unauthorized access by unauthorized parties. By implementing a sliding code cryptographic password security system, this musical instrument store application can provide additional security for users and protect their personal information from cyber threats. In conclusion, the sliding code cryptographic password security application is an effective solution to ensure customer data security and makes it easier for users to search and buy musical instruments online.